Effects of methylphenidate on the aggressive behavior, serotonin and dopamine levels, and dopamine-related gene transcription in brain of male Nile tilapia (Oreochromis niloticus) - Batalhão, Isabela Gertrudes [UNESP]; Lima, Daína; Russi, Ana Paula Montedor [UNESP]; Boscolo, Camila Nomura Pereira; Silva, Danilo Grunig Humberto [UNESP]; Pereira, Thiago Scremin Boscolo; Bainy, Afonso Celso Dias; de Almeida, Eduardo Alves (Springer Nature, 2019)
The occurrence of pharmaceuticals in the aquatic environment has increased considerably in the last decades, causing negative biochemical, physiological, and behavioral effects in aquatic organisms. In this study, we evaluated the effects of methylphenidate (MPH) on the aggressive behavior, dopamine-related gene transcript levels, monoamine levels, and carboxylesterase transcript levels and activity in the brain of male Nile tilapia (Oreochromis niloticus). Carboxylesterase activity was also measured in the liver and gills. Fish were exposed for 5 days to MPH at 20 and 100 ng L−1. Fish exposed to 100 ng L−1 of MPH showed increased aggressiveness and decreased dopamine (DA) and serotonin (5-HT) levels. No changes were observed in plasma testosterone levels and in the transcript levels of D1 and D2 dopamine receptors, dopamine transporter (DAT), and carboxylesterase 2 (CES2). Exposure to 100 ng L−1 of MPH caused a decrease in the transcript levels of carboxylesterase 3 (CES3) and an increase in tyrosine hydroxylase (TH), while exposure to 20 ng L−1 of MPH increased the transcript levels of D5 dopamine receptor. Carboxylesterase activity was unchanged in the brain and liver and increased in the gills of fish exposed to 20 ng L−1. These results indicate that MPH at 100 ng L−1 increases aggressiveness in Nile tilapia, possibly due to a decrease in 5-HT levels in the brain and alterations in dopamine levels and dopamine-related genes.
Keywords: Aggressiveness; Dopaminergic system; Methylphenidate; Nile tilapia; Serotonin